STRATEGI GURU AL-QUR’AN HADITS DALAM MENGATASI KESULITAN BELAJAR AL-QUR’AN SISWA DI MAS YPKS PADANGSIDIMPUAN - Fajriadi, Abdul; Sormin, Darliana; Lubis, Jumaita Nopriani; Wahyuni, Sri (Universitas Muhammadiyah Tapanuli Selatan, 2023)
This study discusses the strategies of Qur'an Hadith teachers in overcoming difficulties learning the Qur'an at MAS YPKS Padangsidimpuan. The purpose of this study was to find out how the strategies of Qur'an Hadith teachers in overcoming students' Qur'an learning difficulties. This study used a qualitative descriptive approach. Data collection techniques use observation, interviews and documentation. The results of the research obtained are. The forms of difficulty learning the Qur'an students at MAS YPKS Padangsidimpuan in the form of students do not understand the makhrajul letters, short length, and tajweednya. Thedifficulty of learning the Qur'anis the factor of the learners themselves, in the form of lack of abilities and knowledge possessed by students, lack of support and guidance from family. School factors and teacher factors. The strategy used in overcomingit is by familiarizing students in reading the Qur'an, taking a psychological approach, practicing reading by the teacher, and the teacher telling students to repeat the reading. While the endalais the lack of interest and focus of students in learning the Qur'an, the lack of ability and knowledge possessed by students and students do not familiarize themselves in learning the Qur'an.